2022
DOI: 10.3389/fmicb.2022.988136
|View full text |Cite
|
Sign up to set email alerts
|

First determination of DNA virus and some additional bacteria from Melophagus ovinus (sheep ked) in Tibet, China

Abstract: Melophagus ovinus (sheep ked) is one of the common ectoparasites in sheep. In addition to causing direct damage to the host through biting and sucking blood, sheep ked is a potential vector of helminths, protozoa, bacteria, and viruses. Sheep M. ovinus samples from three regions in Tibet were selected for DNA extraction. The 16S rDNA V3-V4 hypervariable region was amplified, after genomic DNA fragmentation, Illumina Hiseq libraries were constructed. The 16S rRNA sequencing and viral metagenomics sequencing wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…To date, only ve studies have reported the detection of viruses from M. ovinus [12,20,21,22,23]. In the current study, only the Orf virus and multiple phages were detected.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…To date, only ve studies have reported the detection of viruses from M. ovinus [12,20,21,22,23]. In the current study, only the Orf virus and multiple phages were detected.…”
Section: Discussionmentioning
confidence: 46%
“…More importantly, M. ovinus carries a variety of pathogenic microorganisms that infect the host in the process of sucking blood, such as viruses (e.g., Bluetongue virus [20], Border disease virus [22] and African swine fever virus [23]), Acinetobacter spp. [24] (e.g., Ac.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation